Prophetic Pedagogy: Critically Engaging Public Officials in Rwanda - Thasiah, Victor (Studies in world christianity, 2017)
After genocide, civil war and a complex history of colonial and postcolonial state violence, many within and beyond the African Great Lakes region have called for Rwandan Christians to better maintain critical distance from the state and hold public officials responsible for the flourishing of all, regardless of ethnic identity or political persuasion. The pairing of Rwandan community organising practices and Emmanuel Katongole's political theology offers what I call a prophetic pedagogy for responding to this need. To support this claim, we consider (1) Katongole's theoretical contribution to prophetic Christianity in Africa; (2) the practical contribution of John Rutsindintwarane - the founder-executive director of PICO Rwanda (People Improving Communities through Organizing) - to critically engaging public officials through community organising; and (3) the views of PICO Rwanda's most respected leaders, who demonstrate the potential for holding the Rwanda government accountable. We also use PICO Rwanda's work to develop an effective response to Katongole's sharpest critics.